Exploring multimodal integration in an ESL writing class: teachers’ perspectives - Mohd Karim, Najwa Munira; Ismail, Hanita Hanim (Rsis International, 2025)
This study explores the integration of multimodal approaches in ESL writing classrooms, focusing on teachers’ practices, perceptions, and challenges. Adopting a qualitative phenomenological design, the study collected data through semi-structured interviews with three experienced English instructors from Malaysian tertiary institutions. The findings reveal that teachers employ diverse multimodal strategies—such as visual aids, collaborative tools, and digital platforms—to enhance student engagement and writing skills. Teachers perceive these approaches as beneficial for fostering motivation, participation, and deeper understanding. Despite their potential, challenges such as time constraints, resource limitations, and adapting to diverse student needs hinder implementation. The study underscores the necessity for institutional support, including professional development and access to premium digital tools, to optimize multimodal teaching. These findings offer valuable insights for educators and policymakers aiming to integrate multimodal strategies effectively in ESL writing education, ultimately enhancing learning outcomes in a digitally evolving educational landscape.